Analysis The Use Of E-Ddc In Classification Of Library Materials In Environmental Library Of The Lancang Kuning University - Yulia Putri, Mutia Afifa (Universitas Airlangga, 2021)
This study aims to determine the level of suitability of the classification number of library materials in the Lancang Kuning University Environmental Library based on the use of e-DDC. This research method is descriptive quantitative. The sample in this study is the number of general collections in several libraries at Lancang Kuning University. The results of this study indicate that at the UPT Unilak Library with a sample of 99 collections, the appropriate classification number is 80 collections belonging to very high criteria (81%) while the unsuitable classification number is 19 collections belonging to very low criteria (19%). Furthermore, the Library of the Faculty of Cultural Sciences with a sample of 98 collections, the appropriate classification number is 86 collections belonging to very high criteria (82%) while the unsuitable classification number is 12 collections belonging to very low criteria (12%). Then the Law Faculty Library with a sample of 98 collections, the appropriate classification number is 71 collections belonging to the high criteria (72%), while the unsuitable classification number is 27 collections belonging to the low criteria (28%). Then the Library of the Faculty of Economics with a sample of 97 collections, the appropriate classification number is 75 collections belonging to the high criteria (77%) while the unsuitable classification number is 22 collections belonging to the low criteria (23%). Then the Library of the Faculty of Administration with a sample of 96 collections, the appropriate classification number is 77 collections belonging to very high criteria (82%) while the inappropriate classification number is 17 collections belonging to very low criteria (18%). And the Forestry Faculty Library with a sample of 95 collections, the appropriate classification number is 59 collections belonging to the high criteria (62%) while the unsuitable classification number is 36 collections belonging to the low criteria (38%).